The Application of Student Teams Achievement Divisions (STAD) in Students’ Achievement in Reading Comprehension - Windi Junianti Sitorus; Busmin Gurning (Universitas Negeri Medan, 2013)
ABSTRACT This study aims at improving students’ achievement in reading comprehension applying Student Teams Achievement Divisions (STAD) Method by conducting classroom action research. The subjects of this research ten grade students of SMA Santo Antonius Bangun Mulia Medan. The number of the students was 30 students. There were two kinds of data collected during the study, quantitative and qualitative data. The instrument for collecting the quantitative data was objective test of reading comprehension, while the instruments for qualitative data were gathered through observation sheet, diary notes and check list. Based on the data analysis, the mean of the students score in pre-test 44, in cycle I was 61.16, and in cycle II was 80.33. The conclusion is that Student Teams Achievement Divisions (STAD) method can improve the students’ achievement in reading comprehension. Keywords: STAD Method, Reading Comprehension, Descriptive Text.